Suspected “T-Cell-Mediated” Hypereosinophilic Syndrome Presenting with Cerebral Watershed Infarcts - S. Dujardin; R. Schots; S. De Raedt (Case Reports in Neurological Medicine)
We describe a case of suspected “T-cell-mediated” hypereosinophilic syndrome presenting with cerebral watershed infarcts. An extensive search for potential embolic sources was negative, supporting the hypothesis that cerebrovascular endothelial dysfunction could have caused the infarcts.